PERAN PEMERINTAH DALAM MEWUJUDKAN KOTA LAYAK ANAK (KLA) DI KABUPATEN SIAK TAHUN 2011-2013 - Ambar Setiyani; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Definition of KLA is a county / city having a child rights-based development system through integration commitment and resources of the government, society, and the business thoroughly planned and sustainable in the policies, programs and activities for the fulfillment of children's rights. In order to implement the KLA The district Siak Sri Indrapura well involve government agencies and local communities.This study uses qualitative methode. Data collection techniques used in this study were interviews, observation, and documentation. That is the subject of this research is 7 respondents who include, 1 Kasubag BP3AKB, 1 P2TP2A staff, one person staff KPAID Siak, 1 Public Relations Social Service, 2 PPA Kapolresta, and 1 community Siak.The results of this study indicate that the role of the agency and the community is very important in realizing the implementation of the Suitable Place for Child. KLA goal is to accelerate the fulfillment of the rights and protection of children in Indonesia .. To support the implementation of the city realize the worth of children, the role of government agencies to support and handle cases of child abuse both children as victims and as perpetrators and promote the importance of protecting and fulfilling children. While local communities to support and publicly report any violence case to the authorities in the country. So that the need for better cooperation between government agencies and the community in realizing the City of Eligible Children in Siak.Keywords: Role of Government, and the City of Eligible Children (KLA).